Rebound Intracranial Hypertension: A Complication of Epidural Blood Patching for Intracranial Hypotension - Kranz, P.G.; Amrhein, T.J.; Gray, L. (American Journal of Neuroradiology, 2014)
SUMMARY: Rebound intracranial hypertension is a complication of epidural blood patching for treatment of intracranial hypotension characterized by increased intracranial pressure, resulting in potentially severe headache, nausea, and vomiting. Because the symptoms of rebound intracranial hypertension may bear some similarity to those of intracranial hypotension and literature reports of rebound intracranial hypertension are limited, it may be mistaken for refractory intracranial hypotension, leading to inappropriate management. This clinical report of 9 patients with confirmed rebound intracranial hypertension reviews the clinical characteristics of patients with this condition, emphasizing factors that can be helpful in discriminating rebound intracranial hypertension from refractory spontaneous intracranial hypotension, and discusses treatment. SIHspontaneous intracranial hypotensionRIHrebound intracranial hypertensionEBPepidural blood patchingLPlumbar puncture